2007
DOI: 10.1038/sj.bmt.1705888
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options for the management of acute leukaemia relapsing following an allogeneic transplant

Abstract: The management of acute leukaemia which relapses following an allogeneic stem cell transplant remains a major challenge. In this review we summarize the outcomes of the currently available treatment modalities and discuss emerging novel approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 92 publications
0
23
0
1
Order By: Relevance
“…Treatment options for these patients have been reviewed by Shaw and Russell. 23 They concluded that the main strategies aim at achieving CR by disease-directed therapy and at exploiting the graft-versus-leukemia-effect by immunomodulatory interventions, such as donor lymphocyte infusion (DLI). However, these conclusions were based on small patient numbers in various studies or on retrospective data analyses from registries.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for these patients have been reviewed by Shaw and Russell. 23 They concluded that the main strategies aim at achieving CR by disease-directed therapy and at exploiting the graft-versus-leukemia-effect by immunomodulatory interventions, such as donor lymphocyte infusion (DLI). However, these conclusions were based on small patient numbers in various studies or on retrospective data analyses from registries.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies on combinations of IFN-a and other antileukemic agents offer new opportunities for improving its clinical applicability. 56,80 Such combinatorial approaches have also been reported to be successful in AML patients relapsing after HSCT, 93 arguing for the exploration of new combination regimens. Future research should also focus on identifying the maximally effective IFN treatment scheme with respect to optimal dose, timing and treatment duration.…”
Section: 15mentioning
confidence: 99%
“…10,13 The potential GVL or GVT effects of DLI make it one of the favored treatment choices for recurrent diseases. 14,15 Since Kolb et al first reported sustained remission after DLI in patients with CML relapse after allogeneic BMT in 1990, 16 unmanipulated DLI has become the mainstay allogeneic cellular therapy. However, owing to high risk of GVHD, 17,18 broad use of this monotherapy had been limited until 1996 when an Israeli group described a new approach using lymphocytes treated in vivo or in vitro with recombinant IL-2, by which better therapeutic response was achieved even in those who were previously resistant to unmanipulated DLI.…”
Section: Modified Therapeutic DLImentioning
confidence: 99%
“…These results suggest that low-dose MTX administration post mDLI could lead to stronger GVL effect and less DLI-associated GVHD. 51 Given the risk of high-intensity conditioning regimen and high TRM of a second transplant often chosen for a certain group of patients with relapsed diseases, 15,40,52,53 modified DLI described above could be worthy alternative approaches for those patients. 47 These approaches most likely exert their effect via modulating immune responses.…”
mentioning
confidence: 99%